Measuring Chinese Risk Aversion Based on Insurance Data - Diao, Li (Archives of Business Research, 2020)
In the literature risk aversion has been widely studied by many scholars. However, little research is done about China’s market. In this paper we assume a model involves the insurance data and estimate the risk aversion in China. We use data from 1997 to 2013 after modifying by deflators. The result comes out to support our hypothesis of increasing relative risk aversion.